Organización contable en la empresa comercial del Sr. Chalán Gualán Luis Daniel del cantón Saraguro provincia de Loja, periodo del 01 de octubre al 31 de diciembre del 2023. - Chalán Macas, Leydi Tatiana (2024)
This Curricular Integration Work was carried out in compliance with the requirements established in the Academic Regulations, Art. 216, before obtaining the degree of Bachelor’s in Accounting and Auditing. For the execution of the work, the scientific method was applied in the development of the accounting process, deductive in the literature review, inductive when analyzing the activities and identifying the accounts, analytical in the expression and realization of financial statements, and mathematical in the calculation of operations, the same that was developed with the purpose of emphasize the importance of the accounting process, as well as to make known a reliable result that is evidenced in the financial statements. Through the accounting organization, it was possible to meet the objectives set, where firstly a plan and manual of accounts were designed according to the needs of the company, establishing accounts of assets, liabilities, equity, income, costs, and expenses; an initial inventory was prepared through a physical verification, determining initial values in assets of $ 64,753.81, liabilities with $ 12,649.79 and equity of $ 52,104.02. In addition, auxiliary records of purchases, sales, accounts payable, accounts receivable, and payments were prepared for the subsequent recording of transactions in the daily book using the Multiple Account System and its particularities; The majorization of each account used in the journal was made, passing such balances in the trial balance, placing the accounts with their respective debtor and creditor balances, to subsequently prepare the worksheet with the corresponding adjustments made at the end of the year; Finally, the preparation of financial statements with their explanatory notes where the final balances are reflected and obtaining a profit for the year of $9. 501.69 giving a positive result for the company.